The Role of Learning Styles in the Process of Foreign Language Learning - Qochqorova Zulfizar Abduxamid qizi; Abduboqiyeva Ismigul Ilhomjon qizi (Journal of Innovation in Education and Social Research, 2023)
Learning styles refer to individual preferences and approaches to learning. In foreign language learning, understanding one's learning style can impact how effectively someone grasps new language skills. Some people learn better through visual aids, while others prefer auditory or kinesthetic methods.